SOSIALISASI PENTINGNYA MELANJUTKAN PENDIDIKAN KEPERGURUAN TINGGI PADA REMAJA DI DESA GUNUNG KELAMBU KABUPATEN TAPANULI TENGAH - Rifka Hadia Lubis; Hadijah Sipahutar; Putra Kaslin Hutabarat (COVIT (Community Service of Health), 2022)
This Community Service (PKM) activity is carried out with the aim of creating an additional learning platform by providing socialization or explanations and motivation about how important education is today, as well as generating potential in adolescents and about how to motivate them to continue their education in higher education. It is hoped that a good level of education and adequate skills can improve the quality of human resources so that development can run well too. The method of implementing this activity is to provide socialization that contains (motivation) to youth and the community in Gunung Kelambu village, Badiri sub-district, Central Tapanuli Regency. The results of this activity are expected to increase the understanding of parents in the village of Gunung Kelambu, Kec. Badiri Kab. Central Tapanuli that education is very important so that the youth in Gunung Kelambu Village, Kec. Badiri Kab. Middle Tapanuli. continue their studies to university, and can increase the human resources in the village. Keywords: Education, Higher Education, Community Service